Syntactic and Morphological Selections in the Recitation of Talhah bin Mesrf and His student Hamza bin Habeeb Al- Zayyat: At the end Al-Baqara from verse 282 till end of the surah - Al-Shehri, Wafa Mohammed (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify reading science from the flags of readings (Talha bin Mesrf) one of the followers whose reading was described as abnormal, and his reading interview with the reading of his student Hamza Al-Zayat, and he is one of the seven readers who described their reading frequently, and directed them morally and morphologically, by tracking the verses that were received that, There is a reading by Talha bin Mesrf and his student disagreed or agreed with it and grammatical or morphological analysis of the way in which this reading came out. Therefore, the research relied on a descriptive approach. Frequent and that the reason for the irregularity which is a violation of drawing the Koran, not the weakness of the bond or violation of the rules of the Arabic language.